Aging aggravates cognitive dysfunction in spontaneously hypertensive rats by inducing cerebral microvascular endothelial dysfunction - Mei Wu; Dandan Li; Feng Qiu; Huifang Nie; Rui Fang; Ziyan Zhong; Hui Yang; Xiaoyuan Lin; Xiangyuan Wang; Hongbo Wen; Lijun Gong; Pan Meng (PLoS ONE, 2025)
Hypertension in the elderly can seriously lead to cerebral microvascular damage and promote the development of vascular cognitive impairment. While endothelial function is crucial in cerebral microvascular protection, it is unclear whether aging exacerbates hypertension-induced cognitive dysfunction through endothelial dysfunction. In this study, we injected D-galactose (D-gal) into 24 spontaneous hypertension rats (SHR) and 24 Wistar-Kyoto rats (WKY) for 12 weeks to induce aging. Firstly, the results of behavioral experiments showed that compared with WKY and SHRs injected with D-gal for 0 week, SHRs injected with D-gal for 12 weeks had more severe cognitive dysfunction and memory impairment. Subsequently, the pathological results showed that the pathological changes of brain microvessels and their structural and functional damage were more significant. After that, the results of molecular experiments showed enormous changes in endothelial damage indicators (nitric oxide (NO), endothelin (ET-1), platelet endothelial cell adhesion molecule-1(CD31) and endothelial tight junction protein), aggravation of blood-brain barrier (BBB) damage, microglial activation and upregulation of pro-inflammatory cytokines. Ultimately, the combination treatment of nimodipine and butylphthalide in WKY and SHRs injected with D-gal for 12 weeks showed that the two drugs could hugely improve the cognitive dysfunction in SHRs. In summary, we elaborated that aging exacerbates cognitive dysfunction in SHRs, which may be due to cerebral microvascular endothelial dysfunction, and even BBB damage and neuroinflammation, while the combination of nimodipine and butylphthalide can improve cognitive dysfunction in SHRs, providing a theoretical basis for the treatment of aging and hypertension-related diseases.